Penerapan Permainan Tradisional Berbasis Matematika - Arfatin Nurrahmah; Rita Ningsih (Universitas Serang Raya, 2018)
Mathematics has an important role as aspects of the formation of attitude. Learning mathematics through games traditionally can be used by teachers in carrying out his duty to deliver the material and help the formation of attitudes of the participants his protégé. The activities of this devotion is expected to foster a positive attitude to the students in learning and can change the way the student's point of view towards mathematical subjects. Many traditional games that can be associated with a matter of mathematics. Among them are congkak, engklek, and the bead seats. Through learning with traditional games, students are expected to be more eager to learn math materials. This outreach activity is carried out in SD Negeri Middle 05 Morning located at Jalan Pelita Kingdom RT. 003/RW. 09 Kampung Tengah, East Jakarta. Participants in the activities of the public service this is the teachers and students of SDN 05 Middle morning. The method of implementation of these activities include: observation, documentation, discussion, demonstration, and practice. Activities done with information sharing with teachers of mathematics on alternative delivery and presentation of material that is interesting and fun, one of them using traditional games media-based mathematics. After that describes the media and how to use the Groove provided and any math concepts that fit with the game. In addition to increasing the motivation of children in learning math, the benefits of traditional game among others can develop intellectual intelligence, train motor capabilities, developing emotional intelligence as well as enhance the ability socialize